The occurrence characteristic and dissolution mechanism of lithium-rich sediments in Salt Lake Mahai of Qaidam Basin, NW China - Yanjun Zhao; Pengyu Long; Hua Zhang; Yufei Hu; Zihao Cui; Yumeng Zhang; Minglu Zhang; Qiang Wang; Shengzhong Hu (Scientific Reports)
Abstract The Salt Lake Mahai in Qaidam Basin, western China contains large and thick lithium-rich clay sediments that exhibit great economic potential for lithium exploration. This study analyzed the occurrence of lithium and related dissolution mechanisms in these clay through mineral identification, chemical analyses, and monitoring of brine composition evolution. Our results show that lithium-rich clay mainly occurred as interbeds between salt layers and fillings between salt crystals. The dominant clay mineral is illite, followed by chlorite, kaolinite, and an illite–smectite mixed layer. The leached lithium content in brine was less than 10% of the total lithium content in the clay samples. Lithium commonly occurred as structurally incorporated or adsorbed pattern within the clay minerals, particularly illite, leading to a relatively slow dissolution rate in brine during leaching. Consequently, optimizing the solvent injection points based on the distribution of silt-bearing and clay-bearing halite, particularly in the eastern and northwestern sections of Salt Lake Mahai where leached lithium concentrations are higher (45 ~ 70 mg/L), and extending the contact time between solvent and ore layers could further enhance lithium recovery.